2014
DOI: 10.1038/nature13544
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methylation landscape of human early embryos

Abstract: DNA methylation is a crucial element in the epigenetic regulation of mammalian embryonic development. However, its dynamic patterns have not been analysed at the genome scale in human pre-implantation embryos due to technical difficulties and the scarcity of required materials. Here we systematically profile the methylome of human early embryos from the zygotic stage through to post-implantation by reduced representation bisulphite sequencing and whole-genome bisulphite sequencing. We show that the major wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

57
691
5
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 799 publications
(794 citation statements)
references
References 41 publications
57
691
5
9
Order By: Relevance
“…On the other hand, maternal PN is protected from this demethylation by PGC7 [33]. Recently, it has been reported that the DNA methylation patterns were different between male-and female-derived nuclei in human pronuclear stage embryos [34]. We utilized this phenomenon to identify the origin of the PN in order to reveal the fertilization pattern of abnormal zygotes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, maternal PN is protected from this demethylation by PGC7 [33]. Recently, it has been reported that the DNA methylation patterns were different between male-and female-derived nuclei in human pronuclear stage embryos [34]. We utilized this phenomenon to identify the origin of the PN in order to reveal the fertilization pattern of abnormal zygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Elle présente, elle aussi, une asymétrie parentale lors de la fécondation. Chez la souris comme chez l'homme, le génome du spermatozoïde est plus méthylé que celui de l'ovocyte [10][11][12]. La distribution de la méthylation n'est pas strictement identique dans les deux types de gamètes.…”
unclassified
“…La distribution de la méthylation n'est pas strictement identique dans les deux types de gamètes. Ainsi les ovocytes humains et murins présentent des méthylations en dehors des îlots CpG [10,11]. Ces génomes gamétiques sont globalement déméthylés durant la période s'étendant entre la fécondation et les premiers stades de clivage selon des cinétiques qui peuvent varier selon l'espèce [12].…”
unclassified
See 1 more Smart Citation
“…By comparing the sequences the methylation pattern can be determined. More recently, new methods based on bisulfite conversion and whole genome sequencing have been developed (Guo et al 2014;Salilew-Wondim et al 2015). These platforms can determine the methylation status of thousands of genes at CpG site-level, but are still very expensive and require intensive bioinformatics (data analysis) expertise, which makes it impractical when a large number of treatments or samples are studied.…”
mentioning
confidence: 99%